Salarios, desempleo y productividad laboral en la industria manufacturera mexicana (Wage, Unemployment and Labor Productivity in the Mexican Manufacturing Industry) - López Machuca, José Abraham; Mendoza Cota, Jorge Eduardo (Universidad Autónoma de Nuevo León, 2017)
El artículo evalúa la relación de la productividad laboral y el desempleo con los salarios reales en México durante el periodo 2007 a 2015. Basándose en el modelo de la curva de salarios, la metodología utilizada emplea técnicas econométricas diseñadas para estructuras funcionales estáticas, dinámicas y de cointegración de largo plazo. Los resultados sugieren que los salarios bajos pueden explicarse por la presencia de rigideces importantes, por lo que los salarios guardan una relación inversa con la productividad laboral y el desempleo. Las variaciones en los precios y del salario mínimo no generan cambios significativos en los salarios reales. The article evaluates the relationship between the productivity of labor, unemployment and real wages in Mexico for the period 2007-2015. Based on the wage curve theoretical model, the methodology used for analysis applies static and dynamic econometric techniques for panel data and also long-run cointegration. The results suggest that the low wage level and the slow growth exhibited for several decades could be explained by important rigidities. The estimations showed an inverse relationship of wages with respect to labor productivity and unemployment. The variation of the level of prices and minimum wage did not generate important changes on real wages.